Rancang Bangun Sistem Monitoring Volume Air Pada Tandon Menggunakan Pompa Air Otomatis Bertenaga Solar Cell Berbasis Android - Dwi Chintya Dian Pratiwi; Habibullah Habibullah (Jurnal Teknik Elektro Indonesia, 2022)
Electricity is an irreplaceable part of people's lives, almost all human activities, both in households, offices, and industry. However, in some areas that have not been reached by the Perusahaan Listrik Negara (PLN) , other sources of electrical energy are needed and one solution is to use solar energy which can later be used for daily life, one of which is to turn on the water pump. Based on this problem, the authors made an automatic control system for a solar cell powered DC water pump, where Solar Cell is useful for converting solar energy into electrical energy and in the solar power generation system the method is used Internet Of Thing (IOT), then by using the Pulse With Modulation). In using the monitoring system, we can see the height and volume of the water and display it on the device or application on Android, so that the pump can automatically turn off with the HC-SR04 Ultrasonic sensor to detect value of water level and water volume In the charging system, it can also be seen that the battery charging value is 12.81V, which of course is greater than the value Accumulator so that charging occurs.